Mapping Sovereignty: Cartographic Evidence in Resolving International Boundary Disputes - Dangol, Susheel (Journal on Geoinformatics, Nepal, 2026)
This paper examines the role of cartographic evidence in resolving international boundary disputes and its efficacy in addressing the issue. Review of adjudicated cases from the ICJ, PCA, and UNCLOS tribunals, focusing on disputes where maps played a decisive role identified the patterns in map usages. Four cases settled down by ICJ is selected for the study which includes Preah Vihear case between Thailand and Cambodia, Aouzou strip case between Chad and Libya, boundary dispute between Burkina Faso and Mali, and the case of enclave between the Netherlands and Belgium. The study underscores the dual nature of maps as both technical tools and instruments of territorial claim-making, highlighting the need for standardized cartographic guidelines to mitigate historical discrepancies. The findings contribute to the discourse on conflict resolution by empirically validating the conditional effectiveness of cartographic evidence.